Analysis of drug-related problems identified by future pharmacists in medical wards of tertiary hospitals in the state of Pahang, Malaysia - Elnaem, Mohamed Hassan Abdelaziz; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Jamshed, Shazia Qasi (InPharm Association, 2019)
Objective: Clinical attachments undertaken by pharmacy students in Malaysia are one of the important platforms in order to prepare future candidates for patient-centred pharmacy practice. The lack of data regarding the identification of Drug-related problems (DRPs) and the suggestion of relevant interventions by final year pharmacy students has directed the current research to describe pharmacy students’ abilities in identifying DRPs in their final year clinical placements. Methods: As a descriptive cross-sectional study, it involved the analysis of the clinical case reports of final year pharmacy students during their six-week clinical attachments between February and April 2017 across three different tertiary hospitals in the state of Pahang, Malaysia. A six-member team, who had received the required training by the study’s principal researcher, performed the data extraction from the clinical attachment reports. Results: A total of 385 clinical case reports, identified 880 DRPs. The two most common types of identified DRPs were the untreated condition (17.4 %), followed by inappropriate drug selection (16.3 %). Nearly 47.7 % of total detected DRPs were related to the indication and efficacy domains of therapy assessment. Additionally, there was a positive correlation found between the number of underlying diseases and the number of identified DRP, rs(372) = .14, p = .007. Conclusion: During the final year clinical attachments, the majority of the students were able to identify a considerable number of DRPs in the hospital setting under the supervision of their preceptors. The characterisation of the identified DRPs could be instrumental in refining the experiential clinical learning among future pharmacy practitioners.